The effect of 3 months contraceptive injection on the body mass index of women of reproductive age in the Midwifery Independent Practice of Central Jakarta - Hamidah Hamidah; Dina Sulviana Damayanti (Alma Ata University Press, 2021)
Background: Obesity is increasing in almost all countries in the world and becomes big challenge for the world of health at the moment because it can cause chronic health problems. The increase of obesity occurred is related to the lifestyle of each individual along with the present pandemic condition which carries several consequences caused by change from active behavior into relaxed or sedentary behavior. Because of side effects of weight gain during the use of contraceptive and pandemic routines that change activities, Women of reproductive age gain fat excessively and even lead to obesity. Objectives: The independent variable in this study was hormonal contraceptive (DMPA) and the dependent variables were obesity, age, and duration of hormonal contraceptive (DMPA). The data collected will be tested for normality in advance in order to discover whether the data are normally distributed or not, then will be analyzed by using simple linear regression. This study is expected to provide a reference to suppress obesity in women of reproductive age so the quality of life and reproductive system can be maintained and can bear healthy descendants.Methods: This study had been performed by a quantitative method with chi-square analysis in order to discover the occurrence of obesity with total samples of 385 acceptors of contraceptive in Midwifery Independent Practice in Central Jakarta. Results: The results obtained had indicated that there was no effect on using 3 months contraceptive injection with the occurrence of obesity (p-value = 0.174), and there was no relationship between the duration of using 3 months contraceptive injection and the occurrence of obesity (p-value = 0.467). However significant results were obtained between the age and the occurrence of obesity in acceptors of 3 months contraceptive injection (p-value = 0.013) with a value = 0.05.Conclusions: Women of reproductive age who use 3 months contraceptive injection were expected to be able to maintain their quality of life by preventing excessive weight gain by doing physical activities that can burn calories although it can only be done at home or environment around the house, and doing productive activities during the present COVID-19 pandemic.